Galerie Ernst Hilger : 34. - Galerie Ernst Hilger, Vienna (Wien : Galerie Ernst Hilger Wien, 2009)
Galerie Ernst Hilger Wien ; Picasso, Pablo ; Dubuffet, Jean ; Kolar, Jiri ; Rotella, Mimmo ; Staudacher, Hans ; Rivers, Larry ; Alechinsky, Pierre ; Warhol, Andy ; Hrdlicka, Alfred ; Errò ; Ramos, Mel ; Jones, Allen ; Vitali, Massimo ; Zogmayer, Leo ; Schmalix, Hubert ; marcos, angel ; Buetti, Daniele ; Müller, Josef Felix ; Dorfer, Oliver ; Henning, Anton ; Burns, Ian ; Leikauf, Andreas ; Bussmann, Maria ; Favelli, Flavio ; Franke, Ivana ; Monaco, Julie ; Strukeli, Miha ; Binder, Erik ; Gerrard, John ; Asgar - Gabriel ; Rahbar, Sara ; McKee, Brian ; Khoroshilova, Anastasia
Duits en Engels
Catalogue published on the occasion of the 40th anniversary of the Art Basel, 14.06.2009 - 18.06.2009
boek